The poem that will not end : fun with poetic forms and voices - Graham, Joan Bransfield (Two Lions, 2014)
Ryan O'Brian is riding a wave of inspiration with no shoreline in sight--he can't STOP writing poetry. In the cafeteria with french fries. In the bathroom with toothpaste. Even on the soccer field with mud!